PENGARUH KOMPENSASI DAN PELATIHAN TERHADAP PRODUKTIVITAS KERJA PADA KARYAWAN DI PT ASABA JAKARTA - RONI FASLAH; PUTRI INTAN ASTRINI (Jurnal Ilmiah Econosains, 2014)
Abstract This Study aims to determine whether there is the influence of compensation and training towards productivity of employee in PT Asaba Jakarta. The research was conducted over two month from Mei to June 2014. The research method used is survey method with the correlation approach. From the result of Ftest, found that Fcount (483,263) > Ftable (3,165). This means that X1 and X2 simultaneously affect the Y. T test produce tcount of X1 is (1,715) ≥ ttable (1,673) and tcount X2 (17,653) ≥ t table (1,673). Because t count ≥ t table ,it can be concluded that there is a influence on the job insecurity and organization commitment towards turnover intention. Then a coefficient of determination of test results obtained 0,946 or 94,6% variable Y determined by X1 and X2. Based on the result of regretion model, regression equation obtained is Ŷ = 0,384 + 2,644X1 + 7,010X2 . Beside that, the result of R2 eqqual to 0,946 wich means that compensation and training can explained productivity eqqual to 94,6% and 5,4% explained with another variabel. Keywords: productivity, compensation, training, correlation, regression.